EVALUASI FUNGSI PENGAWASAN KOMISI A DPRD KABUPATEN BANGKALAN TAHUN 2009-2013 (Studi Pada Peraturan Daerah Nomor 07 Tahun 2006) - Dewi, Reza Febriana (Jurnal Mahasiswa Ilmu Pemerintahan, 2014)
ABSTRACT This research entitled the performance of controlling house representative in Bangkalan regency. This research is used a theory of evaluation by Malcom Provus. The technique that is used in collectting the data are interview, documentation and direct observation. This research is taken based on the information from mass-media which report that performance evaluation of house representative in Bangkalan regency is not running well then many of mass-demonstrations happen around the institution. The purposes of this research is to know the performance of commission A house representative in Bangkalan toward the Region Rule Number 07 Year 2006 about the significance result in controlling Region Rule Number 07 Year 2006. The result shows that the performance of commission A house representative in Bangkalan is close to the effective performance. Commission A house representative in Bangkalan follows all the agenda of work that made by deliberation body and it has been controlled by Region Rule. The unsuccessful commission A performance found in monitoring rule region Number 07 years 2006 about the procedures for the selection, Nomination, Appointment and dismissal of the Rapture, the head of the village which is held by Executive. Meanwhile, the point of unsuccessful performance that done by commission A house representative in Bangkalan regency is the Executive has not aggred concret solution given by commission A concerned of problem solving of head executive which is skip the process of head representative election, it makes the rule of region is unsuccessful to be adobted by government. Rule of region Number 07 years 2006 is ill judged law. The solution that given is increment section and article to the rule of region about explicit sanction for those that break the rule of process head representative election. Keywords: Performance Evaluation, House Representative, Controlling Function Â